Big data a business and legal guide - Kalyvas, James R.; Overly, Michael R. (CRC Press, 2015)
Enabling readers to quickly implement solutions with respect to collecting, licensing, handling, and using Big Data, this book provides business people and lawyers with an accessible handbook primer on Big Data and its business implications. All contributors are nationally recognized experts in their fields and each chapter focuses on a different legal issue or risk relating to Big Data.